A review on phase-inversion technique-based polymer microsphere fabrication - Duraikkannu, Shanthana Lakshmi; Castro-Muñoz, Roberto; Figoli, Alberto (Colloid and interface science communications, 2021)
In this review, the preparation method of polymer microspheres (MCs) by phase-inversion is addressed and discussed in detail. An interesting advantage of MCs prepared by the PI method is tailor-made morphology that is a critical factor in separation/adsorption/transport systems. This is relevant since MCs are useful storage device to load chemical, biological components (e.g. drug, enzyme, antioxidant, among others) for physiological and environmental pollution control applications (towards metal ions/organic moieties from different effluents). Different parameters have been reviewed, such as preparation mechanism, the effect of loading material used (e.g. chemical and biomaterials) and their morphologies. Microsized range polymeric materials have been identified as the most suitable in several high-end applications, where the main requirement is a high active surface area and inert host polymer matrix. Several conventional techniques (physical and chemical) have been explored for MCs preparation, as well as the most used structured materials for valuable and sensitive components loading. The current review also compiles the phase-inversion (PI) methodology, as well-adopted membrane preparation protocol, for MCs preparation and the main parameters that influence in their size, shape and loading concentration. Special attention has been given to summarize the MCs (mimic membrane morphology) preparation and its application carried out at ITM-CNR in last decade. [Display omitted] •Assessment of different approaches for microsphere preparation.•Critical review for microsphere fabrication by phase-inversion (PI) technique•Synthetic polymer-based microsphere structure (mimic membranes), shape and nature depend on PI conditions involved•Polymer dope solution physical properties (viscosity, density, etc.,) influence the MC cross section structures